2013
DOI: 10.1371/journal.pone.0083309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Textured Insoles on Balance in People with Parkinson’s Disease

Abstract: BackgroundDegradation of the somatosensory system has been implicated in postural instability and increased falls risk for older people and Parkinson’s disease (PD) patients. Here we demonstrate that textured insoles provide a passive intervention that is an inexpensive and accessible means to enhance the somatosensory input from the plantar surface of the feet. Methods20 healthy older adults (controls) and 20 participants with PD were recruited for the study. We evaluated effects of manipulating somatosensory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
9

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 27 publications
2
65
1
9
Order By: Relevance
“…In studies that investigated more than two treatments (e.g., compression socks and normal socks), the calculated effect size of the multiple treatments was combined and treated as a single effect size for each continuous outcome [51]. Five studies from WGSS [23,24,27,28,52], four studies from TMSS [7,5355], and three studies from SRSS [33,39,56] had more than two treatments in the experimental design. All the effect sizes of the outcomes were then combined as a single effect size for each study.…”
Section: Methodsmentioning
confidence: 99%
“…In studies that investigated more than two treatments (e.g., compression socks and normal socks), the calculated effect size of the multiple treatments was combined and treated as a single effect size for each continuous outcome [51]. Five studies from WGSS [23,24,27,28,52], four studies from TMSS [7,5355], and three studies from SRSS [33,39,56] had more than two treatments in the experimental design. All the effect sizes of the outcomes were then combined as a single effect size for each study.…”
Section: Methodsmentioning
confidence: 99%
“…For example, PC during quiet standing has been routinely used for many years [25,20,33,34,36], with variations including: standing with bare feet [25]; with shoes on [8,4,29]; with eyes open or closed [25,24]; and with legs spaced a fixed distance and arms crossed on chest [17]. PC during quiet stance has also been evaluated over different trial durations ranging from 30 -120 seconds [33].…”
Section: Postural Control (Pc) During Quiet Standing Is An Important mentioning
confidence: 99%
“…Participants were instructed to start from a standing position, with their feet positioned within the boundaries of a predefined area (400 mm wide × 600 mm long), to place the hands by their sides [29], and to maintain an upright standing position for 2 minutes while looking straight ahead. Similar to previous studies, participants wore their shoes during the test with no restriction with regard to foot placement [24].…”
Section: Standing Balance Testmentioning
confidence: 99%
“…14 Other studies have shown that vibration devices and textured insoles were effective in improving postural instability in patients with PD. 10 Altogether, we consider that the foot position changed by a lateral wedge may alter compensatory muscle activation and proprioceptive properties.…”
Section: Discussionmentioning
confidence: 99%
“…COP data recorded at 1,000 Hz were measured for 30 s during quiet standing. 1,10 The primary endpoint is to compare the range and velocity of COP between standing with and without the wedge. The secondary endpoint is to compare the same parameters when a patient's eyes were closed.…”
Section: Methodsmentioning
confidence: 99%